Predictors of Severe Anxiety Among Bumiputera Students - SITI FAIRUS BINTI FUZI; Siti Ramizah Jama; Nordianah Jusoh; Siti Nursyahira Zainudin; Bushra Abdul Halim; Nurul Emyza Zahidi; Wan Hartini Wan Hassan (Information Management and Business Review, 2024)
Despite widespread vaccination efforts, ongoing Covid-19 pandemic continues to affect population globally. In mitigating and exerting control over the spread of the virus, a variety of measures have been carried out by countries worldwide. As a result, this has detrimental effects on citizens’ mental health. University students are particularly among those significantly affected where they face challenges stemming from the pandemic and academic pressures. The purpose of this study was to explore anxiety along with the contributing factors of anxiety itself specifically among the students of Bumiputera at public university. The survey, conducted through a Google Docs Form, was distributed online from 13 Aug to 12 Sep 2021. Descriptive analysis was employed in assessing the anxiety levels of the Bumiputera students. To identify academic features, psychosocial attributes, Covid-19-related factors, socio-demographic characteristics, challenges in open and distance learning (ODL), previously achieved academic performance, current academic performance, and overall satisfaction with ODL that exhibit significant associations with anxiety, an independent-sample t-test or a one-way analysis of variance (one-way ANOVA) was performed. Finally, in identifying protective and risk factors related to anxiety among significant socio-demographic characteristics, ODL challenges, academic characteristics, psychosocial characteristics, COVID-19-related factors and overall satisfaction towards ODL, multinomial logistic regression was conducted. Gender, sharing laptops/computers, difficulties in catching up with tough online courses, depressive thoughts and experience of quarantined because of close contact with positive COVID-19 individuals were identified as protective factors against anxiety symptoms while field of study and overall satisfaction towards ODL were risk factors of developing severe anxiety.